Expectations, Satisfaction and Professional Achievement. An Analysis of their Relation in light of a New Systemic Paradigm: The Three- Dimensional Spiral of Sense - Aparicio, Miriam (European Journal of Social Science Education and Research, 2018)
This research has been done in the field of Education, Sociology and Social and Organizational Psychology. Issues are taken up from two research studies carried out with researchers and PhDs from different disciplinary fields and national contexts. The relationship between Expectations, levels of Satisfaction and Professional Achievement are analyzed in light of different theories: Expectancy-Valence, Attributional theories, Education theories such as Consumption or Investment / Human Capital and the theory of Anomy. The methodology utilized was quantitative-qualitative: two questionnaires, one semi-structured survey including open phrases which allowed actors to speak freely, one interview and, in the case of the French-Argentine research with PhDs, a special qualitative technique was applied: hierarchical evocation. This allowed us to determine which aspects related to professional pathways (objective and subjective) formed part of the “core” of social or shared representations and which were secondary aspects at the periphery of said core. Our findings show non-linear relationships between study variables – Expectations, Satisfaction and Achievement – and self-sustained interplay along three levels: micro individual, meso organizational and macro social. These are interpreted in light of a new systemic paradigm in human and social sciences, a paradigm which the author defines as “The Three-Dimensional Spiral of Sense”.